2022
DOI: 10.1177/23259671221109522
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Grashey View Radiograph for Critical Shoulder Angle Measurement: A Reliability Assessment With Zero Echo Time MRI

Abstract: Background: Suboptimal positioning on Grashey view radiographs may limit the prognosticating potential of the critical shoulder angle (CSA) for shoulder disorders. Purpose: To investigate whether radiography optimized according to the latest research is reliable for measuring CSA in comparison with magnetic resonance imaging (MRI) featuring 3-dimensional (3D) zero echo time (ZTE) sequencing, which accentuates the contrast between cortical bone and surrounding soft tissue with high fidelity. Study Design: Cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…32 Previous studies also did not quantify the amount of glenoid restoration obtained with Latarjet and instead described the amount of glenoid bone loss before performing a Latarjet without reporting coracoid dimensions. 4,33 The changes in humeral head translation observed in the present study are consistent with those of previous studies that demonstrated that anterior humeral head translation increased as glenoid bone loss increased. 4,33 Consistent with these previous studies, we also showed that anterior humeral translation decreased with abduction and external rotation compared with abduction and neutral rotation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…32 Previous studies also did not quantify the amount of glenoid restoration obtained with Latarjet and instead described the amount of glenoid bone loss before performing a Latarjet without reporting coracoid dimensions. 4,33 The changes in humeral head translation observed in the present study are consistent with those of previous studies that demonstrated that anterior humeral head translation increased as glenoid bone loss increased. 4,33 Consistent with these previous studies, we also showed that anterior humeral translation decreased with abduction and external rotation compared with abduction and neutral rotation.…”
Section: Discussionsupporting
confidence: 92%
“…4,33 The changes in humeral head translation observed in the present study are consistent with those of previous studies that demonstrated that anterior humeral head translation increased as glenoid bone loss increased. 4,33 Consistent with these previous studies, we also showed that anterior humeral translation decreased with abduction and external rotation compared with abduction and neutral rotation. Future studies should be performed to examine any differences between Latarjet and distal tibial allograft augmentation without the sling effect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Measurement from frontal radiographs was applied in coronal CT reconstructions. Yıldız et al 9 compared CSA measurement between two observers on coronal reconstructions based on 3D ZTE acquisition; interobserver agreement was excellent on radiographs and good on ZTE, but intermodality agreement was only moderate, with a significant difference between the two approaches.…”
Section: Clinical Interestmentioning
confidence: 99%
“…Recent introduction of commercially available software has facilitated routine implementation of this technique into standard-of-care MR protocols [5][6][7][8]. Benefits of ZTE application in shoulder MRI were previously demonstrated, with strong inter-modality agreements between CT and ZTE images [9][10][11]. As an inherently 3D volume technique, ZTE also accommodates multiplanar reformations and maximum intensity projection renderings, like CT.…”
Section: Introductionmentioning
confidence: 99%